Africans in Colonial Mexico : absolutism, Christianity, and Afro-Creole consciousness, 1570-1640 - Bennett, Herman L. (Herman Lee), 1964- (Blacks in the diaspora., 2003)
"Colonial Mexico was home to the largest population of free and slave Africans in the New World. This book is a study of this population, chiefly in the Mexico City area. It looks at the ways in which slaves and free blacks learned to make their way in a culture of state and religious absolutism. Herman L. Bennett is particularly interested in the way blacks learned to use Spanish and ecclesiastical legal institutions to create a semblance of cultural autonomy, while at the same time enmeshing themselves and their descendants with the dominant culture. This distinctive aspect of Afro-Mexican creolization in an absolutist culture has been little studied. Bennett has gone to the secular and ecclesiastical court records and teased out much new information about the lives of slaves and free blacks, the ways in which their lives were regulated by the government and the Church, the impact upon them of the Inquisition, their legal status in marriage, and their rights and obligations as Christian subjects."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved